Norfloxacin and N-Donor Mixed-Ligand Copper(II) Complexes: Synthesis, Albumin Interaction, and Anti-Trypanosoma cruzi Activity - Darliane A. Martins; Ligiane R. Gouvea; Gabriel S. Vignoli Muniz; Sonia R. W. Louro; Denise da Gama Jaen Batista; Maria de Nazaré C. Soeiro; Letícia R. Teixeira (Bioinorganic Chemistry and Applications)
Copper(II) complexes with the first-generation quinolone antibacterial agent norfloxacin containing a nitrogen donor heterocyclic ligand 2,2′-bipyridine (bipy) or 1,10-phenanthroline (phen) were prepared and characterized by IR, EPR spectra, molar conductivity, and elemental analyses. The experimental data suggest that norfloxacin was coordinated to copper(II) through the carboxylato and ketone oxygen atoms. The interaction of the copper(II) complexes with bovine serum albumin (BSA) and human serum albumin (HSA) was investigated using fluorescence quenching of the tryptophan residues and copper(II) EPR spectroscopy. The results of fluorescence titration revealed that copper(II) complexes have a moderate ability to quench the intrinsic fluorescence of the albumins through a static quenching mechanism. EPR experiments showed that BSA and HSA Cu(II) sites compete with NOR for Cu(II)-bipy and Cu(II)-phen to form protein mixed-ligand complexes. Copper(II) complexes, together with the corresponding ligands, were evaluated for their trypanocidal activity in vitro against Trypanosoma cruzi, the causative agent of Chagas disease. The tests performed using bloodstream trypomastigotes showed that the Cu(II)-N-donor precursors and the metal complexes were more active than the free fluoroquinolone.